Animasi 2D Edukasi Lingkungan tentang Dampak Penebangan Liar di Indonesia melalui Sudut Pandang Surili - Febrian Rohmat Tiansyah (International Forum of Researchers and Lecturers, 2026)
The issue of forest degradation caused by illegal logging in Indonesia poses a serious threat to ecosystem balance and the survival of wildlife. This condition highlights the need for effective visual communication media to deliver environmental education messages in a communicative and easily understandable manner. This study aims to design a 2D educational animation that illustrates the impact of illegal logging on forest ecosystems from the perspective of an endemic animal, the surili. The method used is a qualitative approach with animation production stages consisting of pre-production, production, and post-production. The pre-production stage includes idea development, research, scriptwriting, storyboard creation, and visual design. The production stage involves the creation of visual assets, backgrounds, and animation processes to construct the storyline. The post-production stage includes visual editing, audio integration, and rendering as the final output. The result of this study is a 2D animation entitled “Jaga Lingkungan Hindari Kepunahan Alam,” which presents a structured narrative to effectively convey educational messages. The implications of this work indicate that animation as an educational medium can enhance public awareness of the impacts of illegal logging and emphasize that forest destruction affects not only wildlife but also humans as part of the ecosystem.